Korespondenca med Josipom Stritarjem in Josipom Tominškom v obdobju 1906-1923 - Hriberšek, Matej (Slavistična revija, 2019)
The article examines the yet unpublished correspondence between Josip Stritar and Josip Tominšek between 1906 and 1923 and events that shaped their relationship.
Keywords: correspondence; korespondenca; literarna kritika; literary criticism; Stritar, Josip; Tominšek, Josip